Hiroshima Mon Amour by Marguerite Duras, and “Jabalya Mon Amour” by Rocío Cerón - Monroy Ortiz, Lisbeth Juliana (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper presents a comparative reading of the script Hiroshima mon amour  by Marguerite Duras, and the section “Jabalya mon amour” of the poetry book Empire, by Rocío Cerón, with the objective of reflecting on the particularities of this space of resistance opened up by the arts, particularly literature, in the face of the conclusive self-sufficiency with which they are installed in the functional memory and, subsequently, in the cumulative memory as well (Assmann, 2011). Memories of acts of violence of one people against another; in the specific case of the works– the atomic bomb dropped on Hiroshima by the US army in 1945 and the Israeli government’s bombing of Jabalya, a sector of the Gaza Strip, in 2008. The hypothesis is that the tendency to the conclusive and self-sufficient permanence of these traumatic events in the functional memory, which is evident in the official massified versions, implies a loss of seriousness in the presence of the lived experiences that makes its repetition possible. To this simple tendency, however, literature opposes a treatment of the remembrance of traumatic (collective) events that makes possible to maintain intact the seriousness with which memory should be preserved in functional memory.